Aggregate Economic Shocks and Infant Mortality: New Evidence for Middle-Income Countries - Schady, Norbert; Smitz, Marc-Francois (2012)
We provide country-specific estimates of the effect of macroeconomic shocks on infant mortality for a sample of mainly middle-income countries. In most countries, infant mortality appears to be pro-cyclical or acyclical. Only when shocks to GDP are very deep, 15% or larger, are they consistently associated with higher mortality.